Rotating culture regulates the formation of HepaRG-derived liver organoids via YAP translocation - Shaoyu Zhong; Lu Zheng; Yi Wu; Shujin Sun; Qing Luo; Guanbin Song; Dongyuan Lü; Mian Long (BMC Biology)
Abstract Background Liver organoid serves as an alternative model for liver pathophysiology in carbohydrate or lipid metabolism and xenobiotic metabolism transformation. Biomechanical cues including spaceflight mission can affect liver organoid construction and their related functions, but their underlying mechanisms are not fully understood yet. Here, a rotating cell culture device, namely Rotating Flat Chamber (RFC), was specifically designed for adhering cells or cell aggregated to elucidate the effects of altered gravity vector on HepaRG-derived liver organoids construction. Results The organoids so formed under RFC presented the fast growth rate and large projection area. Meanwhile, the expressions of two pluripotency markers of SOX9 and CD44 were enhanced. This finding was positively correlated with the increased YAP expression and nuclear translocation as well as the elevated α4β6-integrin expression. Inhibition of YAP expression and nuclear translocation decreased the expression of SOX9 and CD44 under RFC, thereby attenuating the pluripotency of HepaRG-derived liver organoids. Conclusions In conclusion, we proposed a novel liver organoid construction method using rotating culture, by which the pluripotency of liver organoids so constructed is mediated by α4β6-integrin and YAP translocation. This work furthered the understanding in how the gravity vector orientation affects the construction of liver organoids and the related mechanotransductive pathways.